El Spatial planning: towards an integration of recent sustainable guidelines (a methodological approach for Autlan de la Grana, Jalisco, Mexico) (2013)
The article presents the methodological approach used in the the city of Autlan de Navarro, which overall scope went from constructing a social cooperating-bonding project  along Autlan de la Grana, Jalisco, Urban Development Plan processes and implementation—, to integrating policies and other spatial planning criteria towards regional sustainability. It addresses three main topics: a) the crisis of urban planning and the search for new horizons, b) constructing a social cooperating-bonding project, and c) Autlan de la Grana Urban Development Plan processes and implementation, which particularly focused on formulating spatial planning policies and guidelines to steer the city’s urban furtherance towards the identification and definition of strategic projects and measures guaranteeing sustainable growth for the benefit of its inhabitants, and lastly, on the way to propelling a culture of social participation among all different members of society and the government.